Application of a Double Aza-Michael Reaction in a ‘Click, Click, Cy-Click’ Strategy: From Bench to Flow - Zang, Qin (2011)
The development of a ‘click, click, cy-click’ process utilizing a double aza-Michael reaction to generate functionalized 1,2,5-thiadiazepane 1,1-dioxides is reported. Optimization in flow, followed by scale out of the inter-/intramolecular double aza-Michael addition has also been realized using a microwave-assisted, continuous flow organic synthesis platform (MACOS). In addition, a facile one-pot, sequential strategy employing in situ Huisgen cycloaddition post-double aza-Michael has been accomplished, and is applicable to library synthesis.